Recycled foam concrete masonry and porcelanite rocks-based lightweight geo-polymer concrete at elevated temperatures - Turkey F.A.; Beddu S.; Al-Hubboubi S.K.; Basri H.B.; Sidek L.M.; Ahmed A.N. (Elsevier B.V., 2025)
This study investigated the mechanical and microstructural properties of lightweight aggregate geo-polymer concrete (LWAGC) produced by alkali-activating glass powder (GP) and Fly Ash (FA) at elevated temperatures ranging from 200 to 800C. It also examined the effects of incorporating crushed foam masonry (RFA) and crushed porcelanite rock aggregates (PA) into FA and GP-based geo-polymer concrete, both before and after exposure to ambient and high temperatures. A low-calcium type of FA was used as a binder in the geo-polymer concrete paste, with a 10 % replacement of glass powder. The concrete samples were heated at temperatures of 200C, 400C, 550C, and 800C for a duration of 60 minutes, with a heating rate of 7C per minute. It was observed that the inclusion of weaker coarse aggregate resulted in a reduction of the compressive strength of the concrete. The geo-polymer concrete was subjected to tests for water absorption, mass loss, cracking, and microstructure analysis at elevated temperatures. The findings indicate that at heating temperatures of 400C and above, the geo-polymer concrete underwent degradation and dehydration. The test findings also revealed residual compressive strengths of 104.9 %, 97.2 %, 81.8 %, and 64.2 % for the (RFA) types, and 107.3 %, 94.8 %, 78.3 %, and 58.8 % for the (PA) types. Additionally, the density decreased by 1.02 %, 4.88 %, 8.10 %, and 13.88 % for (RFA) and (PA) types, respectively, and by 0.27 %, 1.91 %, 4.67 %, and 10.79 % overall. The results indicate that the compressive strength of the concretes increased after exposure to elevated temperatures of 35C and 200C. However, when exposed to temperatures ranging from 400C to 800C, the strength of the LWAGC started to degrade and decline. Based on the obtained findings, the present study recommends performing laboratory tests on construction waste generated during demolition while developing and evaluating numerical models that predict the behavior of the resulting demolition materials when incorporated in the production of geo-polymer concrete. ? 2024 The Authors